Developing Intercultural Citizenship in a Study Abroad Context: Voices of International Postgraduate Students in Britain (Comparative & International Education Series, 2021)
This chapter reports on a qualitative study of eight Kazakhstani postgraduate students’ study abroad experiences, in terms of the extent to which these students actually developed an intercultural citizenship identity as a result of study abroad. Intercultural citizenship refers to ‘the extension of citizenship beyond national borders, through recognition of the global scale of social relations, the need to respect and value diversity, and participation in and responsibility to communities at multiple levels from the local to the global’ (Baker and Fang, 2020, 3). The data collected from a written narrative and three subsequent semi-structured interviews revealed how many participants’ time away from Kazakhstan, combined with the experience of contact with other nationalities and other cultures, gave them the distance necessary to look at Kazakhstan and its culture more objectively. This increased objectivity resulted in developing tolerance of cultural differences, respecting different opinions (e.g., attitudes toward LGBT individuals) and learning to be comfortable in multicultural environments. From this qualitative study, pedagogical implications and areas for ongoing research are suggested.Keywords: Intercultural citizenship, Kazkhstani students, study abroad, qualitative inquiry